Penerapan Combined Compromise Solution dalam Pendukung Keputusan Program Bantuan Pelaku UMKM Kota Lubuklinggau - Primadasa, Yogi; Eluis Bali Mawartika, Yayang; Yandi Saputra, Arie; Hamidani, Syafi'ul (Journal of Digital Ecosystem for Natural Sustainability, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a significant role in strengthening regional economies and providing employment opportunities, particularly in developing cities. The Government of Lubuklinggau City implements assistance programs for MSME actors aimed at enhancing business capacity, competitiveness, and sustainability through funding support, training, and other supporting facilities. In practice, the selection process for aid recipients is often challenging due to multiple evaluation criteria, diverse data, and the potential for subjectivity in assessments. To address these challenges, this study applies the Combined Compromise Solution (COCOSO) method as an optimization approach in the decision-making process. COCOSO is a metaheuristic algorithm that integrates parallel cooperation and information exchange mechanisms among subpopulations, producing more optimal solutions and accelerating convergence. In this research, COCOSO is utilized to process various selection criteria,. The list of alternatives was obtained from the Department of Cooperatives, Small and Medium Enterprises of Lubuklinggau City. The experimental results indicate that this approach provides fairer, more objective, and transparent decision-making compared to traditional methods. Therefore, COCOSO can serve as an effective decision support system to assist the government in distributing MSME assistance programs more accurately and precisely in Lubuklinggau City